2008
DOI: 10.1007/s10681-008-9692-7
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection, combining ability and heritability of coleoptile length in winter wheat

Abstract: Selection of winter wheat cultivars with long coleoptiles is an important component of improving emergence, weed suppression and grain yield in low rainfall regions of the world. Seven winter wheat cultivars were hybridized in a Griffing's half-diallel mating design, method 2 (reciprocals excluded, parents included), model 1 (fixed), and the progeny analyzed for coleoptile length in the F 1 through F 4 for response to selection, general combining ability (GCA), specific combining ability (SCA) and heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Early ground cover is one aspect vital to weed suppression [73] and this trait can be introduced into wheat varieties and was shown to provide a competitive advantage over early emerging weeds and increased resistance to mechanical weeding operations [74]. In wheat, emergence is strongly influenced by coleoptile length, a moderately heritable trait that can be effectively incorporated into modern varieties through breeding [72,75,76].…”
Section: Tolerance To Mechanical Weed Controlmentioning
confidence: 99%
“…Early ground cover is one aspect vital to weed suppression [73] and this trait can be introduced into wheat varieties and was shown to provide a competitive advantage over early emerging weeds and increased resistance to mechanical weeding operations [74]. In wheat, emergence is strongly influenced by coleoptile length, a moderately heritable trait that can be effectively incorporated into modern varieties through breeding [72,75,76].…”
Section: Tolerance To Mechanical Weed Controlmentioning
confidence: 99%
“…The existence of intraspecific variability with respect to osmotic adjustment [6,16,17,19,[20][21][22] and coleoptile growth [23,24] has been demonstrated in different crops. This, along with the possibility of identifying QTLs that control drought tolerance in seedling [25], and coleoptile growth [26], renders the study of coleoptile growth of great interest in the improvement of drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Coleoptile length can also vary because of research or growth conditions. In addition, when we consider the coleoptile lengths reported as 49-119 mm by Schillinger et al (1998), 64-131 mm by Murphy et al (2008a), and 59-159 mm by Murphy et al (2008b), it can be stated that the coleoptile lengths of the bread wheat genotypes used in this study showed narrow variation. Moreover, the fact that the local cultivars and cultivars with old registration dates had longer coleoptiles than the modern and current cultivars took our attention.…”
Section: Coleoptile Lengthmentioning
confidence: 74%
“…Short coleoptiles in seed beds that are unsuitable with respect to moisture and sowing depth decrease yield by extending the duration of emergence, decreasing the number of emergent seedlings, and resulting in smaller leaf area indices and weak seedlings (Richards, 1992;Schillinger et al, 1998). In order to suppress weeds and increase yield, the best practice is to select winter varieties having longer coleoptiles in regions having low rainfall (Murphy et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%